The Spirituality of Ephrem and the Syriac Church in the 4th Century - Vergani, Emidio (Vox Patrum, 2026)
The paper briefly presents Ephrem’s spirituality as emblematic of the earliest Syriac Church, and at least of the fourth century. First, according to Ephrem’s parenesis in his hymns, the truth of Christian witness has to face, with strength and firmness, every testing situation, because of difficulties caused by social or political pressures. Second, it is noted that Ephrem’s vision embraces East and West together, outlining alongside the features of salvation history also those of a geography of salvation. From this emerges a truly universal view of the work of Christ, the true Physician who heals the world described as a great sick body. Finally, some original Ephremian notes are presented on the inseparable solidarity that exists between soul and body, which founds the truth of the Christian hope of resurrection. The necessity, so to speak, of such a promise, which transcends all temporal and spatial order, shines through in the brothers of Bethany, where new life is anticipated, the Lord himself is welcomed and sits at the table among others.